CORRELATION AND PATH ANALYSIS IN F YSIS IN F2 GENERATION OF TION OF MUNGBEAN ( MUNGBEAN (Vigna radiata igna radiata igna radiata (L.) R. Wilczek) ilczek - A.YUSUFZAI SANA; PITHIA, M. S.; D. R. MEHTA; RAVAL, LATA (The Bioscan, 2018)
Twenty six F2 populations of green gram (Vigna radiata (L.) R. Wilczek) were evaluated in Randomized Block Design with three replications during kharif season to study character association for 10 yield and its component characters. There was positive, significant and strong association of seed yield per plant with plant height (rp=0.254 and rg =0.299) and number of pods per plant (rp=0.607 and rg =0.654). Days to maturity had positive, high and significant association with number of branches per plant (rp=0.236), 100- seed weight had positive significant and high correlation with number of seeds per pod (rp=0.303) and number of leaves per plant (rp=0.254), while days to flowering had positive and significant association with number of seeds per pod and negative and significant association with plant height (rp =-0.261) at phenotypic level. Path coefficient analysis at genotypic as well as at phenotypic levels showed that days to maturity (-0.178) negative and plant height (0.226) and 100-seed weight (0.132) made positive high to moderate direct contribution towards seed yield per plant, indicating importance of these characters and can be strategically used to improve the seed yield per plant of green gram.